2022
DOI: 10.3389/fendo.2022.876517
|View full text |Cite
|
Sign up to set email alerts
|

HCG Trigger of GnRH Agonist-Induced Functional Ovarian Cysts Does Not Decrease Clinical Pregnancy Rate in GnRHa Pretreated Frozen Cycles: Evidence From a Retrospective Cohort Study

Abstract: BackgroundGnRH agonist (GnRHa) pretreatment before the frozen-thawed embryo transfer (FET) was increasingly utilized. However, the incidence of GnRHa-induced functional ovarian cysts (FC) was inevitable. The feasibility and efficacy of HCG triggering GnRHa-induced FC are unknown.ObjectiveThe aim of the study was to investigate the effect of HCG triggering GnRHa-induced FC on FET outcomes.MethodsA total of 657 HRT-FET cycles with GnRHa pretreatment were retrospectively analyzed. Patients were divided into the F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…The incidence of GnRHa-induced functional cysts is 9.3% to 9.74%. 36,37 There are conflicting data regarding the impact of ovarian cysts on IVF cycle outcomes. Although some studies have reported decreased number and quality of retrieved oocytes and embryos, and decreased implantation and pregnancy rates among those with GnRHa-induced ovarian cysts, 36,38,39 other studies have demonstrated no difference in IVF outcomes.…”
Section: Pregnancymentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of GnRHa-induced functional cysts is 9.3% to 9.74%. 36,37 There are conflicting data regarding the impact of ovarian cysts on IVF cycle outcomes. Although some studies have reported decreased number and quality of retrieved oocytes and embryos, and decreased implantation and pregnancy rates among those with GnRHa-induced ovarian cysts, 36,38,39 other studies have demonstrated no difference in IVF outcomes.…”
Section: Pregnancymentioning
confidence: 99%
“…One of the known side effects of gonadotropin-releasing hormone agonists (GnRHa), commonly used in vitro fertilization (IVF) treatment, is the development of functional ovarian cysts. The incidence of GnRHa-induced functional cysts is 9.3% to 9.74% 36,37. There are conflicting data regarding the impact of ovarian cysts on IVF cycle outcomes.…”
Section: Special Circumstancesmentioning
confidence: 99%